Hipertensão arterial e doença renal crônica em idosos: revisão das evidências sobre evolução clínica e tratamento - Beatriz Aguiar Medeiros; Julia Gauer Gomides Tavares; Nicolly Cristine Nobre Bredun; Michel Hosananh Vasconcelos (Revista ft, 2026)
Systemic arterial hypertension (SAH) and chronic kidney disease (CKD) are among the most prevalent chronic conditions in the elderly, frequently coexisting and mutually exacerbating their outcomes. This interaction compromises quality of life and increases the risk of cardiovascular and renal complications, making its management a significant challenge. This study analyzed the influence of hypertension on the progression of kidney disease in the elderly and evaluated the effectiveness of available therapeutic strategies. This is a qualitative bibliographic research, based on studies published between 2015 and 2025 in the PubMed, SciELO, LILACS, and CINAHL databases, including full articles in Portuguese, English, and Spanish that addressed the coexistence of SAH and CKD in the elderly. The findings indicate that poorly controlled hypertension is the main factor in the progression of CKD, whose asymptomatic nature favors late diagnosis and increased complications. Therapeutic strategies such as ACE inhibitors, ARBs, diuretics, and non-pharmacological measures proved effective; However, low adherence, polypharmacy, and limitations in follow-up reduce its effectiveness. It is concluded that the association between hypertension and chronic kidney disease requires individualized protocols, educational actions, and early screening in order to improve blood pressure control, preserve renal function, and reduce morbidity and mortality in the elderly.